Gymnosperms of Laos. (10th September 2014) - Averyanov, Leonid V.; Nguyen, Tien Hiep; Sinh, Khang Nguyen; Pham, The Van; Lamxay, Vichith; Bounphanmy, Somchanh; Lorphengsy, Shengvilai; Phan, Loc Ke; Lanorsavanh, Soulivanh; Chantthavongsa, Khamfa
<x xml:space="preserve">Abstract</x> The present review includes keys for identification and summary data on the nomenclature, morphology, ecology and distribution for all 33 species of gymnosperms hitherto recorded in the flora of Laos. They belong to 8 families and 15 genera. Important additions to these data were obtained during fieldwork in 2009–2013, when 58 localities containing 25 species from 14 genera and 8 families were explored and initially studied. Two species, Cycas laotica and Pinus cernua, are described as new species for science. Seven species, Cycas dolichophylla, C. inermis, C. macrocarpa, C. micholitzii, C. nongnoochiae, C. petraea and Taxus wallichiana, are found in Laos and represent new records for the flora of the country. Maps of the distribution and illustrations for the newly discovered gymnosperm species are provided. All observations, records and discoveries are based on reliable scientific literature and collected voucher herbarium specimens housed in main regional herbaria.